Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Someone please help!
Write the function h(x) = -5 (x - 1)^2 + 3 in standard form. ​


Sagot :

Answer:

[tex]h(x)=-5x^2+10x-2[/tex]

Step-by-step explanation:

[tex]h(x) = -5 (x - 1)^2 + 3\\\\\implies h(x) = -5 (x - 1)^2 + 3\\\\\implies h(x)=-5(x^2-2x+1)+3\\\\\implies h(x) = -5x^2+10x-5+3\\\\\implies h(x)=-5x^2+10x-2[/tex]